Resistant Dermatophytosis, the Causative Species, and Treatment - Khudhair Khalaf, Shahad; Fuad Hussain, Anaam; Khalaf Al-Kayalli , Khudhair; Khudhair Khalaf, Amenah (Diyala Journal of Medicine, 2023)
Background: Dermatophytosis was a fungal infection caused by molds (dermatophytes). Dermatophytes are a group of closely related filamentous fungi able to damage and utilize keratin found in the skin, hair, and nails. Objective: To to isolate the species which cause resistant dermatophytosis, and clinical types of tinea, as well as to assess the response to different antifungal therapies. Patients and Methods: Ninety-two patients with different clinical types of tinea infections (ringworm) were seen in a private clinic in Baquba city for the period from May 2021 to December 2021, they were (42) females and (50) males, their ages ranged from (7-70) years with a mean age of (27.57±8) years. All patients were diagnosed clinically as ringworm and supported by isolation of the species from samples either by direct examination of samples or cultures on Sabouraud media, and the patients were treated by combination therapy of systemic and topical terbinafine and systemic azole (itraconazole capsules) for (1-3) months. Results: All patients complained of widespread and concomitant tinea. The most common causative dermatophytes species were Epidermopyton floccosum (44%) and Trichophyton rubrum (22%), less commonly Microsporum audouinii (9.8%), and the others as in Table (1). The most common clinical type was tinea pedis (29.3%) then tinea cruris (26.1%), tinea corporis (22.8%), and tinea ungum (20.7%) as in Table (2). All patients were cured on combination therapy of systemic (terbinafine and itraconazole) and topical (terbinafine). Five patients (5.4%) showed relapses of disease after discontinuation of therapy and retreated by the same method. Conclusion: Epidermophyton floccosum and Trichophyton rubrum were the most common cause of resistant tinea. Terbinafine and itraconazole were good therapeutic options for the treatment of resistant tinea.